A farinograph study on the viscoelastic properties of sago/wheat flour dough systems - Sarker, Md. Zaidul Islam; A., Abd Karim; D. M. A., Manan; A., Ariffin; Nik Ab Rahman, Nik Norulaini; Abd Kadir, Mohd Omar (Elsevier Inc., 2004)
Doughs containing mixtures of sago and wheat flours of differing protein content at different levels of sago substitution (10, 15, 20, 25, 30, 40 and 50%) were prepared as follows: sago + high protein wheat (HPW) flour, sago + medium protein wheat (MPW) flour and sago + low − protein wheat (LPW) flour. The viscoelasticity of doughs from control sago and wheat flours and sago/wheat flour mixtures was determined using a Braberder farinograph. It was found that arrival time increased with increasing protein content in themixture. Peak time for control wheat flours and sago/wheat flour mixtures increased with increasing protein content. Dough stability, 20 min drop and water absorption were found to decrease as the sago proportion in the mixture decreased. The 50% sago/LPW mixture was unable to form a dough. Breakdown times for control HPW flour and HPW flour mixtures were the highest, followed by MPW flour and then LPW flour. However, breakdown time for controlMPW flour was higher than that for HPW flour mixtures. The same trend was observed at all ratios of mixture over the whole experiment.